The Influence of Green Transformational Leadership and Stress on Psychological Well-Being and Quality of Life within Microfinance Institutions in Bandung City - Resawati, Retno; Rinawati, Nenny; Megawati, Imelda; Herawati, Octaviane; Annisa, Dhea Bunga; Andyandi, Pebrio Tri (LPPM STMIK Mardira Indonesia, 2024)
Technology plays a vital role in addressing key challenges in the fashion industry, including high This study investigates the relationship between psychological well-being, quality of life, and green transformational leadership among Bandung City's financial institution's staff members. Using a non-parametric approach and SEM PLS technique, data from 276 randomly selected respondents were used to analyze the impact of inspiring leaders and an environmentally friendly work environment on individuals' Psychological Well-Being and their assessment of their quality of life. The results showed a positive relationship between psychological well-being and quality of life and between psychological well-being and green transformational leadership. This research aims to promote sustainable human resource management practices and policies by offering insightful information.